Performing Gender: Female Masculinity in D. H. Lawrence’s The Rainbow - Gurung, Gol Man (Molung Educational Frontier, 2020)
This paper analyses Ursula, the female protagonist of D. H. Lawrence’s the novel The Rainbow, who reflects her masculinity. Many feminist critics have perceived this novel as man-centered. In response to this analysis of the novel, the paper tries to look at the novel from the perspective of Judith Halberstam’s theoretical concept of female masculinity, especially Ursula as a masculine woman who acts like a man. Female masculinity is not an identity but a site for identification where different identities can flourish, but masculine women possess confidence, assertiveness, and independence. Lawrence gives justice to women’s role by presenting Ursula as a new woman who seeks her individual identity in the traditional world. Through the reading of the novel as its theoretical tool, the research concludes that females can be as males and males can be like females. She acts like a man and that means she has masculine qualities. The novelist portrays Ursula as a woman with masculinity because she can flourish different identities of her life. She plays the role of an independent woman, a liberated woman, a Lesbian woman, and a new woman, etc. She behaves like a tomboy who refuses to accept the Victorian conventions of society. So, she is a masculine woman rather than a feminine woman. This paper emphasizes how a woman can perform like a man; this suggests masculinity is not the private property of a male; it is a social position that can be practiced in an individual way.